Using Jigsaw Learning Methodology to Foster Active Learning About Pulmonary Infections - Ricardo Gonzalez-Rothi; Irene Alexandraki (Association of American Medical Colleges, 2015)
Abstract Introduction Clinical concepts may be difficult to integrate in the preclinical years but are necessary for the development of clinical reasoning skills. The integration of basic sciences with clinical sciences throughout the 4 years of undergraduate medical education may better prepare physicians for clinical medicine. This resource seeks to horizontally and vertically integrate the microbiology of pulmonary pathogens taught to second-year students during their microbiology course with the reality of the pulmonary bedside practice through the use of clinical case vignettes. Horizontal integration brings together two or more disciplines to understand a topic, while vertical integration applies basic science concepts to the assessment and management of a patient in a clinical scenario. We used small-group instruction as it allows active involvement of the students in the educational process, and chose an innovative small group methodology, the Jigsaw Classroom, that has not been previously used in this context. Methods This resource consists of a presession exercise and a jigsaw exercise designed to be complementary to didactic materials on the topic of potential pulmonary pathogens. Students are divided into small groups and given a case to review. Each group is required to identify the two most likely pathogens that could cause the pulmonary infection based on the context of the setting, history, and physical findings of the case. The small groups then rearrange into jigsaw groups where each student presents their case to the others. A clinician and basic scientist serve as facilitators. Results This resource was geared to and presented to second-year medical students in the context of a Medical Microbiology course at our institution (class size = 120). The voluntary post-jigsaw survey results demonstrated an excellent response rate (89 out of 120 students = 74%). The survey was designed to assess various aspects of the exercise using a Likert scale. Approximately 87% of survey completers either agreed or strongly agreed that the pre-session exercise provided them an appropriate framework for the small-group work. Eighty-seven percent agreed or strongly agreed with the statement: "I can integrate and apply the didactic materials on pulmonary pathogens that we have had in the course this semester in a manner that makes sound clinical sense." Discussion The jigsaw exercise was designed to be complementary to didactic materials learners have had in various large-/small-group settings on the topic of potential pulmonary pathogens and to materials they are concomitantly learning in their doctoring skills (history taking, physical examination, and clinical reasoning) and pathology courses. The format could potentially be used to teach other topics as an effective way to link basic sciences with clinical medicine in medical schools with integrated curricula.